The Expression of miRNA223 that related with lipid profile in chronic kidney disease patients - Shukur, Shahad Ayad; Hussein, Sahar M. (Iraqi Journal of Science, 2025)
Chronic kidney disease (CKD) is a major public health concern and a leading cause of mortality worldwide. This study aimed to explore the relationship between the expression of microRNA-223 (miRNA-223) and the prevalence of chronic renal disease, with a focus on identifying potential biomarkers in Iraqi patients. The study found a correlation between blood lipid profiles and the risk of developing CKD. A total of 250 blood samples were collected, 150 samples from CKD patients and 100 samples control group were collected from healthy individuals. Clinical biomarkers showed that there was a significant increase (p-value ≤ 0.05) in white blood count, neutrophil, lymphocyte, blood urea and creatinine, while the increase in platelet count was not significant (p-value≥ 0.05). Additionally, analysis of serum lipid levels revealed a significant difference between the two study groups according to triglycerides, high-density lipoprotein and very low-density Lipoprotein (p-value < 0.01) which was 219.3±141.2, 36.16±11.8 and 42.77±26.33 respectively. However, there were no significant differences in total cholesterol and low-density Lipoprotein levels, which were 186.5±63.45 and 96.37±37.44 (p-value ≥ 0.05) in the patient group compared to the healthy controls group. A molecular study was done through analysis by (RT-qPCR) quantifying miRNA-223 expression as a novel biomarker for the disease. The folding expression of mi-RNA 223 showed down-regulation in the patient compared to the control group (0.322±0.32vs 1.00).